THE INTRODUCTION AN INSTITUTE OF FOSTER FAMILY AS ALTERNATIVE FORM OF INTERCALATION CHILDREN, WHO HAVE NOT PARENTS - Boiko , J. (Theory and Practice of Public Administration, 2020)
The article is dedicated by the research of state’s regulation of foster family. The author analyzed the genesis of the introduction of foster family as alternative form of intercalation children, who have not parents. The main attention was focused on the advantages of a foster family, as alternative form of intercalation children, who have not parents. Also, the main attention was focused on features state regulation of foster family’s action. In addition, the author was researched the advantages of foster family, as alternative form of intercalation children, who have not parents. The introduction and development of foster family, as optimal form of intercalation children, who have not parents, was argued in this article. So, there are a lot of advantages of foster family in compared with other form of intercalation children, who have not parents. A foster family is expedient form of intercalation children, who have not parents for state and for children too. Moreover, fosterage ensure the right to family. The child retained all insurances, which prescribed in the law for child in orphan. Also, the child doesn’t lose biological parental care, he or she may keep in touch with parents, if parents don’t constitute a threat to their child. A foster family allow to children in orphan and children, deprived of parental care to have a family. And persons, who have not a child for various reasons, may bring up a foster child. Moreover, the government doesn’t lose control of a foster parents’ activities. Also public authorities monitor respect for the rights of foster children. Foster family has some financial support by the state. Thus, a foster family have an opportunity to develop. The interaction between foster families and public authorities are achieved by a child serves. A child serves identifies problems in foster family and helps parents to search ways of dealing with problems. The author analyzed aspects of institute of foster family, which requires completion and creation documentation and laws.